2010
DOI: 10.13004/jknts.2010.6.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Subdural Hematoma Presenting with Falx Syndrome after Trauma

Abstract: Interhemispheric subdural hematoma (ISH) presenting with falx syndrome is a rare occurrence. We present a case of ISH presenting with falx syndrome with visual disturbances. A 66-year-old woman reported headache as a result of a fall. Initial nonenhanced computed tomography (CT) showed a left frontal ISH. Two days later, she was noted to have right homonymous hemianopsia and marked right hemiparesis, especially in the right lower extremity. Follow up CT demonstrated an increase in the size of the frontal ISH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
2
0
8
Order By: Relevance
“…The most common cause of this lesion is trauma, especially over the occipital region, accounting for 80% to 90% of cases. 10 11 14) As the pathogenic mechanism of posttraumatic IHSDH, tearing of the parasagittal bridging veins were proposed by some authors, 2 5 7) however, the origin of this hematoma actually identified by surgery was veins in the IH fissure, branches of pericallosal artery or brain laceration in the IH fissure. 16) …”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of this lesion is trauma, especially over the occipital region, accounting for 80% to 90% of cases. 10 11 14) As the pathogenic mechanism of posttraumatic IHSDH, tearing of the parasagittal bridging veins were proposed by some authors, 2 5 7) however, the origin of this hematoma actually identified by surgery was veins in the IH fissure, branches of pericallosal artery or brain laceration in the IH fissure. 16) …”
Section: Discussionmentioning
confidence: 99%
“…These veins are stretched by the tangential forces. 10) A2 arteries are neighbored with bridging vein. In our case, the forces of falx affected A2 artery and adventitia of vessel was injured.…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte izole interhemisferik subdural hematom (İSH) posttravmatik intrakraniyal kanamanın en nadir formunu oluşturmaktadır. İlk kez 1940'da otopside ve 1955'de de yaşayan bir kişide saptanmıştır (5).…”
Section: Introductionunclassified
“…ISH genellikle kafa travmasından sonra görülmekte olup spontan veya nontravmatik gelişimi ise çok nadirdir (5,6). İSH klinik tablosunu sıklıkla alt ekstremite monoparezisi veya bacaklarda belirgin olan hemiparezi ile karakterize olan falks sendromu oluşturmaktadır (5,7).…”
Section: Introductionunclassified
See 1 more Smart Citation